2005
DOI: 10.1086/502610
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Nosocomial Infections in a Neurologic Intensive Care Unit

Abstract: Neurologic intensive care patients have relatively high rates of device-associated nosocomial pneumonia and UTI. For a valid comparison of surveillance data and implementation of targeted prevention strategies, we would strongly recommend provision of national benchmarks for the neurologic ICU setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
1
13
1
4
Order By: Relevance
“…All our patients were recipients of medical devices. Prolonged mechanical ventilation (MV) is known to an important risk factor for Clostridium difficile infection on NICU [17] and in our study the median length of MV pre CDAD was 7 (4)(5)(6)(7)(8)(9)(10)(11)(12) days.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…All our patients were recipients of medical devices. Prolonged mechanical ventilation (MV) is known to an important risk factor for Clostridium difficile infection on NICU [17] and in our study the median length of MV pre CDAD was 7 (4)(5)(6)(7)(8)(9)(10)(11)(12) days.…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies have described Clostridium difficile infection on NICU either as a proportion to all nosocomial pathogens identified on NICU or in those with a new fever following NICU admission [10][11][12]. Clostridium difficile has been reported to account for between 0.6 and 4.7% of all nosocomial infections on NICU and is responsible for 4% of new fevers (C38.3°C) on NICU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Main characteristics of patients in neurological intensive care unit *statistically significant **chronic heart disease, chronic obstructive lung disease, hypertension, chronic hepatic and renal disease hospital stay. On the other hand, in a study conducted at a neurological ICU in Germany, Zolldann et al [19] reported an HI incidence rate of 21.0% and density of 24.8 per 1,000 patient-days of hospital stay. An earlier study conducted in the same country [20] reported somewhat higher values with a incidence rate of 24.2 and density of 25.0.…”
Section: Discussionmentioning
confidence: 95%
“…The proportion of these infections in similar studies conducted in the world is smaller and ranges from 36.6% to 42.9% [19,22], although urinary tract infections do not represent the most common HIs found in hospitals worldwide [23]. One of the important factors for the high incidence of urinary tract infections in our hospitals is the lack of national guidelines and measures to control these infections.…”
Section: Discussionmentioning
confidence: 98%